2021
DOI: 10.3390/diagnostics11081441
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Properties of Three SARS-CoV-2 Antibody Tests

Abstract: Serological assays emerged as complementary tools to RT-PCR in the diagnosis of SARS-CoV-2 as well as being needed for epidemiological studies. This study aimed to assess the performance of a rapid test (RT) compared to that of serological tests using finger prick blood samples. A total of 183 samples were evaluated, 88 of which were collected from individuals with negative RT-PCR and 95 from positive RT-PCR individuals. The diagnostic performance of RT (WONDFO®) and LUMIT (PROMEGA®) were compared to that of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The findings revealed that antibody responses were highly heterogeneous between individuals and assays, consistent with previous reports [ 21 28 ]. Comparable trends in antibody response kinetics observed between the different assays suggest that the different antigen targets (NP, N and S) were similarly immunogenic.…”
Section: Discussionsupporting
confidence: 91%
“…The findings revealed that antibody responses were highly heterogeneous between individuals and assays, consistent with previous reports [ 21 28 ]. Comparable trends in antibody response kinetics observed between the different assays suggest that the different antigen targets (NP, N and S) were similarly immunogenic.…”
Section: Discussionsupporting
confidence: 91%
“…SARS-CoV-2-specific serum total Ig assays. SARS-CoV-2 spike protein-specific total antibody titers were measured using the Lumit Dx SARS-CoV-2 Immunoassay (Promega Corp.) (42). The test detects total Ig specific for the RBD antigen within the SARS-CoV-2 spike protein.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid lateral flow assay is a valuable tool for diagnosing and monitoring various diseases [ 39 , 40 , 41 , 42 ]. To date, rapid diagnostics of COVID-19 to determine the antigen and the presence of IgG/IgM antibodies to SARS-CoV-2 to prevent the spread of the virus is carried out using lateral flow tests [ 43 , 44 ]. In parallel, other methods of virus identification are being developed, including electrochemical sensors, colorimetric tests, and SERS sensors [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%